2002
DOI: 10.1073/pnas.202471299
|View full text |Cite
|
Sign up to set email alerts
|

A potent analog of 1α,25-dihydroxyvitamin D 3 selectively induces bone formation

Abstract: 1,25-Dihydroxyvitamin D3 [1,25(OH)2D3] is a principal regulator of calcium and phosphorus homeostasis through actions on intestine, kidney, and bone. 1,25(OH) 2D3 is not considered to play a significant role in bone formation, except for its role in supporting mineralization. We report here on the properties of 2-methylene-19-nor-(20S)-1␣,25(OH) 2D3 (2MD), a highly potent analog of 1,25(OH)2D3 that induces bone formation both in vitro and in vivo. Selectivity for bone was first demonstrated through the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 25 publications
2
160
1
Order By: Relevance
“…A previous study (65) has suggested that calcitriol dose-dependently exhibited inhibitory effects on osteoblastic activity. Thus, although we are unable to rule out an effect of calcitriol in producing the ABD in our animal model, the dose and the actions of 1,25(OH)2D3 in previous studies (57,58,61) suggest that it may not have been the cause of the ABD we observed.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…A previous study (65) has suggested that calcitriol dose-dependently exhibited inhibitory effects on osteoblastic activity. Thus, although we are unable to rule out an effect of calcitriol in producing the ABD in our animal model, the dose and the actions of 1,25(OH)2D3 in previous studies (57,58,61) suggest that it may not have been the cause of the ABD we observed.…”
Section: Discussioncontrasting
confidence: 62%
“…Studies have shown that vitamin D-deficient animals infused with calcium and phosphate had similar histomorphometry, bone growth, and mineralization compared with animals supplemented with vitamin D, and the mineralization defect is directly due to insufficient calcium and phosphorus in plasma at sites of mineralization (59,60). Recent studies have shown that even higher doses of calcitriol greater than were used here did not decrease bone formation in ovariectomized rats (61). In transgenic mice deficient in the 1␣-hydroxylase gene (CYP27B1), a marked decrease in skeletal modeling and growth is observed corrected with a rescue diet that normalizes the serum calcium.…”
Section: Discussionmentioning
confidence: 59%
“…5A). 2MD is known to induce RANKL expression in osteoblastic cells (20,21). Then, RANKL was injected into CSF-1 op/op mice, but neither the osteoclast formation nor the increase in erosion surface (ES/BS) was observed (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Primary calvarial osteoblasts (mOBs) were obtained as previously described [9] and cultured in α-MEM. Human osteosarcoma MG63 cells were grown in Dulbeccos's modified Eagle's medium (DMEM) supplemented with 1% non-essential amino acids.…”
Section: Cell Culturementioning
confidence: 99%